Susceptibility of TNF-α-deficient mice to Trypanosoma congolense is not due to a defective antibody response - Naessens, Jan; Kitani, H.; Momotani, E.; Sekikawa, K.; Nthale, J.M.; Iraqi, F.A. (Elsevier, 2004)
C57BL/6 mice deficient in one or two copies of the gene for tumor necrosis factor alpha (TNF-α) were more susceptible to Trypanosoma congolense infection than their resistant, wild-type counterparts. The number of TNF-α genes was correlated with the capacity to control parasitaemia and with survival time. Absence of TNF-α resulted in a diminished capacity to form germinal centres in lymph nodes and spleen. Since germinal centres are involved in antibody production and affinity maturation, the susceptibility of the TNF-α-deficient mice could have been due to this secondary defect. Despite the lack of the germinal centres, the antibody responses to internal and exposed trypanosome antigens and to non-trypanosome antigens were not significantly different. Also the relative avidities measured in infected sera did not significantly differ between the two mouse strains. These data suggest that the role of TNF-α in control of T. congolense was not due to its role in the development of an antibody response.